Les femmes en temps de pandémie dans les médias - Martin Blanc; Valérie Yanick; Johanna Massé; Richard Khoury; Julie Alice Gramaccia (Communication)
This article presents the main public communication studies in French and English addressing how women were represented in the media during the first three years of the COVID-19 pandemic. It is part of a broader research effort to use artificial intelligence to better understand how women were represented in the Quebec press during COVID-19 (OBVIA, Université Laval). The literature review was conducted from a feminist and intersectional perspective. One of the major findings of our review is that women were underrepresented in the media during the pandemic. Although a several articles discussed women as figures of authority, particularly in a political context, a significant portion focused on women from the perspective of care, based on themes such as domesticity, motherhood, and caregiving (where the figure of the healthcare worker is dominant). To a lesser extent, other studies addressed the issue of gender-based violence. Our study also highlights the lack of significant French-language contributions on the representation of women in the media during the first three years of the pandemic.